COVID-19: A Heuristic Justification of Presidency as a Rhetorical Institution (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
When a country is faced with a crisis, the President, as the chief policy maker and Head of State, is the first person expected to act. With the power vested in him by the Namibian constitution in the article 26 (1), Hage Geingob, the President of Namibia declared a State of emergency on 17 March 2020 in response to the global pandemic Coronavirus (COVID-19). A national crisis is one of the important occasions of a presidency as a rhetorical institution. In this regard, words are an important source of power. Therefore, this paper analysed the language and rhetoric of emergency used by Geingob as his political tool to respond to this pandemic. The analysis is guided by the rhetorical theory (Bitzer, 1968) and Aristotle’s rhetorical proofs of ethos, pathos and logos. It is important to note that national crises such as COVID 19 are linguistic constructions in the sense that it is largely through presidential rhetoric that the country deals with them.
Keywords: COVID-19; Coronavirus; Rhetoric; Presidency; Crisis; Politics; Language